2017
DOI: 10.1016/j.aller.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The relation of innate and adaptive immunity with viral-induced acute asthma attacks: Focusing on IP-10 and cathelicidin

Abstract: Innate immunity biomarkers such as serum IP-10 and cathelicidin can be used to predict viral-induced acute asthma. These biomarkers may provide potential new treatment targets for acute asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Abundant data support the hypothesis that CXCL10 functions as a biomarker for severe asthma and virus-, especially rhinovirus-, induced asthma [21][22][23]. The level of CXCL10 is reported to be higher in asthmatic sputum than in healthy subjects [24], and higher in acute asthmatics' serum compared to serum from controlled asthmatics [25]. In vitro, addition of Th2 cytokines to virus-infected cells elevated release of CXCL10 [26], and CXCL10 itself induced adhesion of eosinophils to ICAM-1 and release of EDN from eosinophils [27].…”
Section: Discussionmentioning
confidence: 93%
“…Abundant data support the hypothesis that CXCL10 functions as a biomarker for severe asthma and virus-, especially rhinovirus-, induced asthma [21][22][23]. The level of CXCL10 is reported to be higher in asthmatic sputum than in healthy subjects [24], and higher in acute asthmatics' serum compared to serum from controlled asthmatics [25]. In vitro, addition of Th2 cytokines to virus-infected cells elevated release of CXCL10 [26], and CXCL10 itself induced adhesion of eosinophils to ICAM-1 and release of EDN from eosinophils [27].…”
Section: Discussionmentioning
confidence: 93%
“…According to Huang et al [ 53 ] and Xiao et al [ 57 ], cathelicidin concentration in sputum may be a biomarker separating COPD from asthma. Furthermore, two studies (20%) by Arikoglu et al (2015) and Arikoglu et al (2017) found lower LL-37 levels in stable asthma versus asthma exacerbations [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Greiller et al (2019) conducted experiments as part of their vitro study to evaluate the effect of vitamin D on responses of respiratory epithelial cells to infection with rhinoviruses, a common respiratory tract pathogen [ 59 ]. Greiller et al (2019) linked vitamin D effects to increased expression of cathelicidin [ 59 ]. However, the clinical study conducted by Arikoglu et al (2015) only partially validated the conclusion of Greiller at al.…”
Section: Resultsmentioning
confidence: 99%
“…CXCL10 secreted by epithelial cells may participate in airway in ammation and AHR through activation and recruitment of immune cells. CXCL10 can interact with CXCR3, which is expressed on activated CD4 + , CD8 + and NKT cells, mast cells and eosinophils, and stimulates the migration of these cells [30].The presence of mast cells in the airways is characteristic of asthma. Viral infection may lead to the release of CXCL10 in the bronchial epithelium, which activates mast cells and allows them to migrate to airway smooth muscles to exacerbate airway in ammation and bronchoconstriction in asthma [31].…”
Section: Discussionmentioning
confidence: 99%